Upaya Meningkatkan Hasil Belajar Peserta Didik dengan Penerapan Pendekatan TaRL (Teaching at The Right Level) pada Mata Pelajaran IPAS Kelas V UPT SDN 060843 Medan Barat - Nadia Nan Dinanti; Mimi Rosadi; Dara Fitrah Dewi; Emce Ida Hutabarat; Rizka Padilah (Departement of Mathematics Education, 2024)
The use of learning approaches that never change has an impact on low learning outcomes in the subject of science, this analysis was conducted to apply the Teaching at The Right Level (TaRL) learning method to improve the learning outcomes of the subject of science of class V students of UPT SD Negeri 060843 Medan Barat. This study uses the Classroom Action Research (CAR) method which will be carried out in 2 cycles. This study involved 20 students of class V of UPT SD Negeri 060843 Medan Baratconsisting of 10 males and 10 females. The results of the study showed that in the pre-cycle stage the average learning outcomes of students were 35% and in cycle I there was an increase, namely an average of 65% of students and in cycle two there was an increase of 100%. From these results it can be concluded that the Teaching at The right Level (TaRL) learning approach is effective in improving the learning outcomes of the subject of science of class V students of SD Negeri 060843 Medan Barat.